Evaluation of Correlations between Underlying Disease and Port Complications - Teichgräber, U.; Nagel, S. N.; Kausche, S. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: Evaluation of correlations between underlying disease and port complications.Materials and Methods: Retrospective analysis of a data set of 3160 port systems, which had been interventionally implanted over a period of 10 years. Of these, 1393 were included in the final evaluation. The 7 most common underlying diseases and port-induced complications were considered. Port-related thrombotic events, port pocket infections as well as the port-induced sepsis were evaluated and classified as either early or late complications.Results: In 1393 ports, 131 experienced complications. Of these, 22.1 % (n = 29) were early and 79.6 % (n = 102) late complications. The overall incidence rate of late complications was 0.253/1000 observed days. It differed significantly between the underlying diseases (p < 0.001) and was significantly lower in colon carcinoma when compared with pancreatic (p = 0.049), gastric (p = 0.012) and bronchial carcinoma (p = 0.042). The incidence rate of the port sepsis between the underlying diseases also differed significantly (p = 0.006) and had the highest rate in gastric and bronchial carcinoma. The occurrence of a thrombotic event also showed a significant difference in the incidence rates between the underlying diseases (p = 0.045) and was highest in pancreatic and gastric carcinoma.Conclusion: There are significant differences in the incidences of complications between the underlying diseases. Knowledge about this can help to improve the port-care and to take specific preventive measures.Key Points:• significant differences in the incidences of port complications between underlying diseases• incidence rate of late complications significantly lower in colon carcinoma compared to pancreatic, gastric and bronchial carcinoma• highest incidence rate of port sepsis in gastric and bronchial carcinoma• highest incidence rate of thrombotic events in pancreatic and gastric carcinoma• studies on specific prophylactic measures requiredCitation Format:Teichgräber U, Nagel SN, Kausche S Evaluation of Correlations between Underlying Disease and Port Complications. Fortschr Röntgenstr 2014; 186: 496 – 500
Keywords: vascular; interventional procedures; catheters